PSV-18 Time Since Last Meal Until the Onset of Farrowing Affects Survivability of Newborn Piglets. (12th April 2022) - Gao, Xin; Zhao, Junmei; Hu, Qiong; Chan, Lawrence
Abstract: The present study aimed to investigate whether time since last meal until the onset of farrowing affects sow reproductive performance. The results are based on data records compiled from 8 batches for a total of 660 mixed parity (µ = 3.7) sows from the same commercial farm. All sows were fed standard lactation diets twice a day (7:30 AM and 4:30 PM) 1 week before expected farrowing. Time since last meal until the onset of farrowing and farrowing duration were calculated accordingly. Based on the time from the start of last meal to the onset of farrowing, sows were divided into three groups: 0-3 hours, 3-6 hours and 6-16 hours (212, 220 and 228 sows respectively). Probability of born alive, stillborn and mummified piglets were statistically analyzed by a binomial model in R. Farrowing duration of sow was not affected by time since last meal until the onset of farrowing. However, sows farrowed 3-6 hours after feeding had lowest probability of stillborn piglet compared with sows farrowed 0-3 hour and 6-16 hour after feeding (6% vs 8% and 10%; P < 0.01), greater probability of born alive was also found in sows in 3-6 hour group than the other 2 groups (92% vs 89% and 88%; P < 0.01). The probability of mummified piglet was not affected when comparing the three groups. Time since last meal until the onset of farrowing also showed no effect on litter size or litter birth weight. In conclusion, feeding sows the last meal 3-6 hours before farrowing may help improve live born and decrease stillborn piglets.